Метод статистичного аналізу текстів драматургії Б. Шоу і розмовного стилю - Хомицька, І.; Теслюк, В. (Видавництво Львівської політехніки, 2015)
Проаналізовано фоностатистичні структури текстів підстилю драматургії та розмовного стилю. Доведено, що середні частоти груп приголосних фонем є критерієм диференціації зіставлених текстів. Побудовано модель визначення ступеня взаємодії текстів художнього (підстиль драматургія) та розмовного стилів. Встановлено ступінь проникнення елементів розмовного стилю в підстиль драматургії художнього стилю за чотирма з восьми груп приголосних фонем, за якими статистичним методом визначено істотні відмінності. Phonostatistical structures of the texts of the substyle of drama and colloquial style have been analyzed. Mean frequency of occurrence of groups of consonant phonemes has been proved to be differentiation criterion of the compared texts. A model has been built to determine the degree of interaction of the texts of the belles-lettres (substyle of drama) and colloquial styles. The degree of penetration of elements of the colloquial style into the substyle of drama of the belleslettres style has been established by four out of eight groups of consonant phonemes by which essential differences have been determined by statistical method.
Keywords: середня частота груп приголосних фонем; фоностатистична структура; позиція фонеми в словi; mean frequency of occurrence of groups of consonant phonemes; phonostatistical structure; position of a phoneme in a word